Photodynamic therapy of circumscribed choroidal haemangioma. Issue 11 (15th October 2004) - Singh, A D; Kaiser, P K; Sears, J E; Gupta, M; Rundle, P A; Rennie, I G
Abstract : Aim: To evaluate efficacy of verteporfin ocular photodynamic therapy (PDT) in treatment of 10 patients with a symptomatic circumscribed choroidal haemangioma. Design: Prospective non-randomised, interventional case series and critical review of previously published studies. Methods: 10 consecutive patients (seven primary, two failed transpupillary thermotherapy (TTT), and one failed external beam radiotherapy) with symptomatic circumscribed choroidal haemangioma were treated using verteporfin 6 mg/m 2 given as an intravenous infusion over 10 minutes. Diode laser (690 nm) with an intensity of 600 mW/cm 2 for 83 seconds (50 J/cm 2 ) was applied 5 minutes after completion of infusion. Single or multiple partially overlapping spots were applied based on the tumour basal dimensions. Periodic follow up with ophthalmoscopy, ultrasonography, and angiographic studies was performed. Results: All 10 patients showed evidence of regression with flattening of tumour, resolution of subretinal fluid, and reduction of choroidal vasculature on angiograms. The visual acuity either improved or remained stable in eight (80%) patients. Visual loss due to delayed choroidal atrophy was seen in two patients. Conclusions: Although verteporfin PDT is an effective treatment for management of symptomatic circumscribed choroidal haemangioma, delayed treatment related effects can lead to visual loss.